Growth phase significantly decreases the DHA-to-EPA ratio in marine microalgae - Boelen, Peter; van Mastrigt, Audrey; van de Bovenkamp, Henk H.; Heeres, Hero J.; Buma, Anita G. J. (Aquaculture international, 2017)
Microalgae are the principal producers of long-chain polyunsaturated fatty acids (LC-PUFAs) such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) in marine ecosystems. Algae are used in aquaculture systems as direct or indirect feed for zooplankton, filter-feeding mollusks and larval stages of crustaceans and fish. Therefore, it is necessary to select nutrient-rich strains, with high levels of EPA and/or DHA, preferably during the stage of rapid growth. During the course of algal growth (exponential to stationary phase), many microalgal species accumulate lipids, especially triacylglycerols. However, relatively little is known about the effect of growth phase on LC-PUFA accumulation. In the present study, absolute and relative EPA and DHA levels of seven representative species of marine microalgae were determined during different growth phases in batch culture. Four species ( Phaeodactylum tricornutum , Thalassiosira weissflogii , Thalassiosira pseudonana and Rhodomonas salina ) accumulated fatty acids during growth. In all these species, intracellular EPA levels were higher during the late stationary growth phase than during exponential growth. In contrast, an increase in DHA content was not observed and therefore the DHA-to-EPA ratio was significantly lower in late stationary phase cultures. These results can be used to improve the nutritional value of microalgae cultivated for application in marine aquaculture systems.